Molecular characterization of bread wheat (Triticum aestivum) genotypes using SSR markers - DEVI, SUMAN; SINGH, VIKRAM; YASHVEER, SHIKHA; DALAL, MOHINDER SINGH; PARAS,; CHAWLA, RUKOO; AKBARZAI, DARYA KHAN; CHAURASIA, HARSH (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted during winter (rabi) seasons of 2019–20 and 2020–21 at the research farm of CCS Haryana Agricultural University to study the genetic diversity of 80 bread wheat (Triticum aestivum L.) genotypes, using 43 polymorphic SSR markers. A total of 84 alleles were discovered, with an average of 3 alleles amplified per locus. The average value of the allelic PIC varied from 0.26 to 0.82. Primers, viz. Xgwm 129, Xgwm 131, TaGST, CFA2147, Xwmc48, Xbarc 1165 and Xwmc169 may be deemed particularly informative given their high PIC values. Indices of dissimilarity varied from 0.14 to 0.42. Eighty wheat genotypes were clustered into two main groups with 35 and 45 genotypes each using the dendrogram constructed on the basis of molecular data of polymorphic markers. Using STRUCTURE, genotypes were classified into 4 major sub-populations having Fst values 0.351, 0.363, 0.508 and 0.313, respectively. Future breeding operations in wheat cultivars for tolerance to abiotic stress should consider genotypes clustering into different groups. Assessing the molecular genetic diversity is a reliable approach to identify cultivars by analyzing of specific regions of the cultivars DNA based on their unique genetic profiles.